The contribution of pulses to net zero in the UK - Horril, M; Maguire, R; Ingram, J (IOP Publishing, 2024)
The UK agrifood sector is estimated to be responsible for a quarter of the UK’s territorial greenhouse gas emissions, making it a priority sector for the UK’s net zero commitments by 2050. Pulses have been commonly identified as significant in driving emissions reduction throughout the value chain, whilst also delivering multiple co-benefits for biodiversity, soils, local economy, and human health. This review takes a food systems perspective on the potential of pulses to help achieve net zero in UK agrifood. It explores how pulses can increase the net zero impact of each of the key activities and their associated stakeholders: producers, processors and manufacturers, transportation and storage operators, consumers, and waste handlers. In so doing, the review contributes to a field which tends to focus on the two ends of the value chain (production and consumption), as these have been the areas of main interest to date. It thereby accentuates the ‘missing middle’ (what happens between the farm gate and the plate) in mainstream net zero discussions. While it identifies many opportunities in all food system activities along the entire value chain, it also discusses the significant social, economic and technological barriers to increasing the production and consumption of pulses in the UK. Knowledge of producing pulses has dwindled, yields are not economically competitive, the infrastructure to support processing lacks investment, and consumer behaviour is only slowing shifting towards a more pulse-rich diet. A coordinated shift is required across the pulse system to capitalise on the overall net zero opportunities from ‘fork to farm’.